ANALISIS PRINSIP-PRINSIP EKONOMI ISLAM DALAM PENGGUNA SHOPEEPAYLATER - Rahmadhani, Nayla; Putra, Budi Jaya (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Shopee Paylater is one of the innovations in the form of digital payments that is increasingly popular among the public in the era of the digital economy. However, from the perspective of sharia economics, the use of this feature raises various debates regarding its compliance with sharia principles, especially regarding the prohibition of usury, gharar (uncertainty), and masyir (gambling). This research applies a qualitative method with a literature approach to examine the practice of Shopee Paylater based on sharia economic principles. The findings of this study show that Shopee Paylater has elements of usury due to interest and penalties, and potentially contains gharar and masyir due to uncertainty in fees and the risk of default. In addition, the ease of access to Paylater can trigger consumer behavior that is not in line with Islamic values. Thus, it is important to provide Islamic financial education to consumers and establish strict regulations so that digital payment practices can follow economic principles.